Butterfly count on different habitats in international institute of tropical agriculture (IITA), Ibadan-Nigeria (2022)
Butterflies are considered as good ecological indicators for other invertebrate and as surrogate representatives of environmental quality changes. Their occurrence and diversity in populations contribute to thriving ecosystems and can indicate the state of an ecosystem’s health. Though, there is high increase in habitat fragmentation of most protected area. However, information on butterfly species abundance, richness on different habitat is limited in the study area. The study assessed the diversity and abundance butterfly species in relation to its environmental factors. Sampling was done quantitatively using three complementary methods, line transect (walk-and-counts), hand nets, and fruit bait traps in June and July 2018. Data was analysed using descriptive statistics, diversity indices and Pearson’s correlation. A total of 646 individual representing 40 butterfly species belonging to 5 families in the order Lepidoptera were recorded across the three different habitats. Members of Nymphalidae family occurred most and accounted for 57.5% species and 63.3% total number of individual species with Acrsea serena been the most dominant across the habitats. Forest habitat had the highest species composition (n = 316). Generally, species abundance (31.0%), richness (33.7%) and family composition (33.7%) respectively, were recorded more through visual count method, while mean species abundance (26.1%) encountered higher with hand-net method. There was no significant relationship between the environmental factors and the total number of individuals or species richness. But rainfall was found to be positively correlated with the species diversity and abundance. Hence, understanding the factors affecting butterfly species diversity and abundance in IITA is very important for conservation purposes.